2020
DOI: 10.15376/biores.15.3.4866-4885
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the awareness and readiness of the Malaysian furniture industry for Industry 4.0

Abstract: The lack of knowledgeable and skilled workers is a major challenge faced by the Malaysian furniture sector. It hinders industrial productivity and its ability to move up the value-chain by adopting high technology. Therefore, in order to assess the awareness and readiness of the Malaysian furniture industry for Industry 4.0, a questionnaire-based survey was conducted with a sample of 778 large-, medium-, and small-sized furniture manufacturers throughout Malaysia. This study is part of an on-going Erasmus+ pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 27 publications
3
18
0
Order By: Relevance
“…Realistically, changes in design media are nothing new, particularly in the Industry 4.0 era (Ratnasingam et al, 2020;Romero-Gázquez et al, 2020;Oxman, 2008). However, this study found that the ID field's frequent challenges come from the changes in processes rather than changes in the architectural knowledge base.…”
Section: Design Pedagogy In the Industrial Design Fieldmentioning
confidence: 79%
“…Realistically, changes in design media are nothing new, particularly in the Industry 4.0 era (Ratnasingam et al, 2020;Romero-Gázquez et al, 2020;Oxman, 2008). However, this study found that the ID field's frequent challenges come from the changes in processes rather than changes in the architectural knowledge base.…”
Section: Design Pedagogy In the Industrial Design Fieldmentioning
confidence: 79%
“…Consequently, the demand for skilled and competent workers for operating and controlling DT may also be limited, further aggravating the prevailing mismatch between the human capital developed through the Wood Science and Technology (WST) curriculums at several universities in the country and the employment opportunities available in the industry (Ratnasingam et al 2018b). In this context, policy makers must take cue from this revelation that encouraging the adoption of DT in labor intensive manufacturing industries, must also be supported with the employment of skilled and competent workforce to manage and support such technologies (Ratnasingam et al 2020b). Such a transformation must however be implemented by first reducing the number of foreign contract workers, who appear to be a restraint on such a transformation.…”
Section: Implications Of the Studymentioning
confidence: 99%
“…The way designers and stakeholders think about design during the evolution of Industry 4.0 is now totally different (Abidin et al, 2018;. According to Ratnasingam et al (2020), the lack of knowledgeable and skilled workers to handle Industry 4.0 technology is a concern among furniture manufacturers. Therefore, the proposed university-level Industry 4.0 programme may provide substantial benefits in training furniture workers in the future.…”
Section: Issues Of Education and Trainingmentioning
confidence: 99%